AN ASSESSMENT OF THE IMPLEMENTATION OF DIFFERENTIATED INSTRUCTION IN PRIMARY SCHOOLS, KABWE DITRICT, ZAMBIA - Adebayo, Awoniyi Samuel; Shumba, Christine Banda (European Scientific Journal, ESJ, 2014)
The purpose of the study was to determine the degree to which the implementation of differentiated instruction was carried out in Primary schools. The research design was descriptive. The population for the study consisted of all the 43 Primary schools of Kabwe District with a total population of 1817 teachers. The sample for study was made up of 15 randomly selected schools and 241 teachers selected using the simple random sampling technique. The instrument for the study was a selfconstructed questionnaire of the five point Likert scale. The questionnaire was face and content validated and the reliability of the instrument determined using the Cronbach’s alpha reliability method following a pilot study using 30 respondents from two schools that were not part of the main study. An alpha reliability coefficient of 0.740 was obtained. The data collected were coded and analysed using the Statistical Packages for Social Sciences (SPSS). The descriptive statistics and regression analysis were employed. The study revealed that differentiated instruction was implemented in schools. Findings from the study revealed that teachers frequently adapted the curriculum to pupils’ needs and were sensitive to learners needs.Teachers frequently used classroom strategies in the implementation of differentiated instruction, they enjoy administrative support however teaching materials were not available in all subjects. Regression analysis revealed that administrative support and learners’ background accounted for 37% and variance in the implementation of differentiated instructions. Administrative support accounted for 27.2% while learners’ background accounted for 9.8%.Administrative support therefore is a major factor in the implementation of differentiated instruction. The more there is administrative support, the more the implementation of differentiated instruction. It was recommended that school administrators needed to give more support in the area of resources for the successful implementation of the programme.